DESKRIPSI DAN PENYAJIAN TOKOH PADA WACANA BERITA KASUS e-KTP DALAM PERSPEKTIF PERS NASIONAL - Zamzani, Zamzani; Wahyudin, Ahmad; Rahayu, Yayuk Eny (Fakultas Bahasa, Seni, dan Budaya, Universitas Negeri Yogyakarta, 2021)
(Title: Description and Presentation of Characters in The News in The Case of e-KTP in National Press Perspective). This study aims to describe the presentation of figures in the e-KTP case news discourse involving Setya Novanto. The research design used is a qualitative descriptive study with a critical discourse analysis perspective, especially the Fairclough model (1995: 58). The data source of this research is the news about the e-KTP case involving Setya Novanto in Kompas, Republika, and Media Indonesia. The data collection technique was done by observing and taking notes. The validity of the data used in this study were content validity and pragmatic semantics. The reliability of this study uses an intrarater and discussions with peers. Based on the results of the analysis, several things were found related to the description of the characters in the e-KTP case. The representation of the identity of the actors in the e-KTP case is presented in different ways in each media. In these three media, only Republika tends to be more detailed and complete in representing the character (the identity of the perpetrator). The depiction of identity begins with the mention of the perpetrator's name, position, wife, children, nephews, and religion. Kompas puts more emphasis on facts relating to the perpetrators. Not everything related to the perpetrator is revealed. Meanwhile, Media Indonesia is more focused on the involvement of other actors.Keywords: the e-KTP case, Setya Novanto, national press perspective